A novel NR3C2 polymorphism and the increased thyroid-stimulating hormone concentration are associated with venlafaxine treatment outcome in Chinese Han MDD patients. (February 2020) - Yuan, Fan; Yuan, Ruixue; Ren, Decheng; Bi, Yan; Niu, Weibo; Guo, Zhenming; Wu, Xi; Xu, Fei; Sun, Qianqian; Ma, Gaini; Yang, Fengping; Zhu, Yuhao; et al.
Abstract: Objective: We aimed to study the association among venlafaxine antidepressive outcome, NR3C2 gene polymorphisms and the change of two neuroendocrine hormones during treatment. Methods: 195 Chinese Han major depressive disorder (MDD) patients were recruited and received a 6-week venlafaxine treatment in this study. Adrenocorticotropic hormone (ACTH), thyroid-stimulating hormone (TSH) levels were measured at the beginning and at the end of treatment. Six single-nucleotide polymorphisms (SNPs) ( NR3C2 : rs1512325, rs1512342, rs2070951; NR3C1 : rs6191, rs6196, rs10482614) were selected for high-throughput SNP genotyping. Allele and genotype frequencies of them were compared between remission and non-remission groups. Results: We found that genotype frequency of the rs1512325 located in the NR3C2 gene was significantly different between remission and non-remission groups respectively ( p < 0.05). Meanwhile, the frequency of the rs1512325 C-allele was significantly lower ( p < 0.05) in remission group. The TSH concentration significantly increased after venlafaxine treatment in remission group ( p < 0.05). Conclusion: The rs1512325 in NR3C2 gene and TSH concentration may be related to venlafaxine treatment outcome in Chinese Han MDD patients.